Evaluation of a synthetic single‐crystal diamond detector for relative dosimetry on the Leksell Gamma Knife Perfexion radiosurgery system. Issue 9 (5th August 2015) - Mancosu, Pietro; Reggiori, Giacomo; Stravato, Antonella; Gaudino, Anna; Lobefalo, Francesca; Palumbo, Valentina; Navarria, Piera; Ascolese, Anna; Picozzi, Piero; Marinelli, Marco; Verona‐Rinati, Gianluca; Tomatis, Stefano; et al.
Abstract : Purpose: To evaluate the new commercial PTW‐60019 synthetic single‐crystal microDiamond detector (PTW, Freiburg, Germany) for relative dosimetry measurements on a clinical Leksell Gamma Knife Perfexion radiosurgery system. Methods: Detector output ratios (DORs) for 4 and 8 mm beams were measured using a microDiamond (PTW‐60019), a stereotactic unshielded diode [IBA stereotactic field detector (SFD)], a shielded diode (IBA photon field detector), and GafChromic EBT3 films. Both parallel and transversal acquisition directions were considered for PTW‐60019 measurements. Measured DORs were compared to the new output factor reference values for Gamma Knife Perfexion (0.814 and 0.900 for 4 and 8 mm, respectively). Profiles in the three directions were also measured for the 4 mm beam to evaluate full width at half maximum (FWHM) and penumbra and to compare them with the corresponding Leksell GammaPlan profiles. Results: FWHM and penumbra for PTW‐60019 differed from the calculated values by less than 0.2 and 0.3 mm, for the parallel and transversal acquisitions, respectively. GafChromic films showed FWHM and penumbra within 0.1 mm. The output ratio obtained with the PTW‐60019 for the 4 mm field was 1.6% greater in transverse direction compared to the nominal value. Comparable differences up to 0.8% and 1.0% for, respectively, GafChromic films and SFD were found. Conclusions: The microDiamond PTW‐60019 is a suitable detector for commissioning and routine use of Gamma Knife with good agreement of both DORs and profiles in the three directions.